Performance analysis outcome of a 19‐MWp commercial solar photovoltaic plant with fixed‐tilt, adjustable‐tilt, and solar tracking configurations. (30th August 2021) - Chandel, Rahul; Chandel, Shyam Singh
Abstract: Photovoltaic (PV) plants are generally installed at optimum tilt angle for a location or using sun tracking for enhancing energy generation potential. The objective of the present study is to assess the practicability of these techniques for large commercial plants along with determining expected uncertainty in simulated energy yield estimation. In this study, performance analysis of a 19‐MWp (17‐MWac ) PV plant is carried out which is installed in India with fixed‐tilt (FT), seasonal adjustable‐tilt (AT), and horizontal single‐axis solar tracking (HSAT) configurations. This study is the first‐time comparative power enhancement analysis of these three different configurations under real outdoor conditions for a single large scale power plant at one location. The operation and maintenance issues of these configurations are also analyzed. A reliability analysis of linear actuator of the industrial solar tracking system is carried out as the actuator is a critical part of the solar tracking system of the power plant. Major results of the study are annual performance ratio 79% (FT), capacity factors = 19% (FT), 20% (AT), and 22% (HSAT) respectively, final yields (Yf ) = 4.58 h/day (FT), 4.85 h/day (AT), and 5.28 h/day (HSAT). The energy yield simulations are done on two widely used PV design software: PVSyst and PVSOL and results are analyzed in detail. The accuracy of predicted data is validated and found to be within acceptable limits of uncertainty. The results of this study are compared with previous studies. Abstract : A first‐time comparative power enhancement analysis of 19‐MWp photovoltaic (PV) plant with fixed‐tilt, seasonal adjustable‐tilt, and horizontal solar tracking system is presented along with realiability analysis of an industrial solar tracking system. The horizontal single axis tracking and adjustable tilt systems show an energy enhancement in comparison to fixed‐tilt PV arrays despite operation and maintenance problems. Results of software simulation uncertainty analysis indicate predictions to be under acceptable limits.